Unprecedented flexibility of the 1, 1′-bis(o-carborane) ligand: catalytically-active species stabilised by B-agostic B–H⇀Ru interactions12. Issue 3 (14th December 2015) - Riley, Laura E.; Chan, Antony P. Y.; Taylor, James; Man, Wing Y.; Ellis, David; Rosair, Georgina M.; Welch, Alan J.; Sivaev, Igor B.
Abstract : The compound ( p -cymene)Ru[(C2 B10 H10 )2 ], an effective Lewis acid catalyst, is the precursor to a number of products in which the 1, 1′-bis( o -carborane) unit displays an unprecedented range of ligating modes. Abstract : Doubly-deprotonated 1, 1′-bis( o -carborane) reacts with [RuCl2 ( p -cymene)]2 to afford [Ru(κ 3 -2, 2′, 3′-{1-(1′-1′, 2′- closo -C2 B10 H10 )-1, 2- closo -C2 B10 H10 })( p -cymene)] (1 ) in which 1, 1′-bis( o -carborane) acts as an X2 ( C, C ′)L ligand where "L" is a B3′–H3′⇀Ru B-agostic interaction, fluctional over four BH units (3′, 6′, 3 and 6) at 298 K but partially arrested at 203 K (B3′ and B6′). This interaction is readily cleaved by CO affording [Ru(κ 2 -2, 2′-{1-(1′-1′, 2′- closo -C2 B10 H10 )-1, 2- closo -C2 B10 H10 })( p -cymene)(CO)] (2 ) with the 1, 1′-bis( o -carborane) simply an X2 ( C, C ′) ligand. With PPh3 or dppe1 yields [Ru(κ 3 -2, 3′, 3-{1-(1′-1′, 2′- closo -C2 B10 H10 )-1, 2- closo -C2 B10 H10 })(PPh3 )2 ] (3 ) or [Ru(κ 3 -2, 3′, 3-{1-(1′-1′, 2′- closo -C2 B10 H10 )-1, 2- closo -C2 B10 H10 })(dppe)] (4 ) via unusually facile loss of the η-( p -cymene) ligand. In3 and4 the 1, 1′-bis( o -carborane) has unexpectedly transformed into an X2 ( C, B ′)L ligand with "L" now a B3–H3⇀Ru B-agostic bond. Unlike in1 the B-agostic bonding in3 and4 appears non-fluctional at 298 K. With CO the B-agostic interaction of3 is cleaved and a PPh3 ligand is lost to afford [Ru(κ 2 -2, 3′-{1-(1′-1′, 2′- closo -C2 B10 H10 )-1, 2- closo -C2 B10 H10 })(CO)3 (PPh3 )] (5 ), which exists as a 1 : 1 mixture of isomers, one having PPh3 trans to C2, the other trans to B3′. With MeCN the analogous product [Ru(κ 2 -2, 3′-{1-(1′-1′, 2′- closo -C2 B10 H10 )-1, 2- closo -C2 B10 H10 })(MeCN)3 (PPh3 )] (6 ) is formed as only the former isomer. With CO4 affords [Ru(κ 2 -2, 3′-{1-(1′-1′, 2′- closo -C2 B10 H10 )-1, 2- closo -C2 B10 H10 })(CO)2 (dppe)] (7 ), whilst with MeCN4 yields [Ru(κ 2 -2, 3′-{1-(1′-1′, 2′- closo -C2 B10 H10 )-1, 2- closo -C2 B10 H10 })(MeCN)2 (dppe)] (8 ). In5 and6 the three common ligands (CO or MeCN) are meridional, whilst in7 and8 the two monodentate ligands are mutually trans . Compound1 is an 18-e, 6-co-ordinate, species but with a labile B-agostic interaction and3 and4 are 16-e, formally 5-co-ordinate, species also including a B-agostic interaction, and thus all three have the potential to act as Lewis acid catalysts. A 1% loading of1 catalyses the Diels–Alder cycloaddition of cyclopentadiene and methacrolein in CH2 Cl2 with full conversion after 6 h at 298 K, affording the product with exo diastereoselectivity (de >77%). Compounds1–8 are fully characterised spectroscopically and crystallographically.